Student Behavior Management and Tracking Software Using RFID and QR Code Combine with IoT Technology, Case Study : Lubosama School - Mansattha, Muhammad; Ruangkarn, Rachata; Benjapolakul, Watit (Princess of Naradhiwas University Journal, 2019)
Unrest situations occur continuously in the Southern border provinces of Thailand affecting the development of education to people in this area. Students lack of educational opportunities resulting in school achievement with below national average. One of problems found was truancy. The researchers proposed a solution for this problem by implementing RFID and QR code technology integrated with IoT that adopt digital technology via mobile application. This application used to monitor student attendance, and compared students’ learning achievement between the 1st semester (pre-test), and the 2nd semester (post-test) in academic year 2018. The results found that after using system, the average learning achievement of students (11.58 %) was improved. The findings suggest that the RFID and QR Code combined with IoT technology should be proposed to other schools in three Southern border provinces of Thailand.